(untitled) (Scientia Agropecuaria, 2019)
Identifying the ideal product is the most important step in new product development and improvement of existing ones. The aim of this study was to identify the ideal smoked bacon using PrefMFA and PrefMap considering three different sensory spaces obtained via descriptive analysis (DA), projective mapping (PM) and CATA questions. Six smoked bacons were characterized by ten trained assessors using DA, and by two consumers panel using PM (n=93) and CATA questions (n=100). Also, one hundred consumers indicated their overall liking using a nine-point hedonic scale. The results showed that both techniques identified an ideal product. However, the sensory method has a greater effect than the multivariate procedure to obtain the sensory spaces prior to the preference mapping. Subsequent studies with other food matrices are still necessary in order to generalize our results.